PELATIHAN DAN PENDAMPINGAN PERCEPATAN PUBLIKASI KARYA TULIS ILMIAH BAGI GURU MAN 2 JEMBER - Wahyu Eko Widiyanto; Christine Wulandari Suryaningrum; Alvionita Eka Septi; Sarwendah Intan; Goegoeh Pangestu (Jurnal Pemantik, 2023)
Writing scientific papers is a very important activity for a professional teacher. This activity not only needs to be carried out in order to obtain credit points for promotion or for certification purposes through a portfolio, but moreover it needs to be carried out in order to improve the quality of class management, service quality to students, and also increase professionalism. Training and assistance in accelerating the publication of scientific papers will be held on March 12, 2022. This activity will be held in the front hall of MAN 2 Jember. The activity was attended by 22 teachers from the fields of mathematics, Indonesian, English, Physical Education, Pancasila and Citizenship Education, and Biology. This training consists of four stages, namely the training stage, question and answer session, practice or practice and mentoring. Competence in writing articles, adjusting writing to the journal template to be addressed, as well as partners getting knowledge that is indeed in accordance with partner needs.